Grievance Resolution: Perceived Goal Interdependence and Interaction Patterns - Tjosvold, Dean; Morishima, Motohiro (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1999)
This study identifies behaviours and perceptions of the individuals involved that affect grievance resolutions. Based on conflict research, the study proposes that cooperative goals promote the direct, open-minded consideration of opposing views which leads to quality solutions efficiently developed. Management and union representatives in two large Western Canadian forest product companies were interviewed about grievances they had handled that were and were not settled within their committee. They first described in detail a recent, significant grievance and then answered specific questions to code the incident. Structural-equation results and the analysis ofthe qualitative data suggest that cooperative goals induce the open-minded discussion of diverse views, which in turn results in high-quality, integrative solutions. However, with competitive goals, managers and employees interacted close-mindedly and were unable to agree upon integrative solutions efficiently. If replicated, the framework developed can help structure cooperative interdependence and guide skill training in grievance handling.